2014
DOI: 10.1021/ie500694c
|View full text |Cite
|
Sign up to set email alerts
|

Combined Production of Polymeric Birch Xylan and Paper Pulp by Alkaline Pre-extraction Followed by Alkaline Cooking

Abstract: Alkaline pre-extraction of birch wood was performed to isolate polymeric xylan and subsequently produce a paper-grade pulp. At 95°C and 2.5 mol/L NaOH, 7% of wood was transferred to the E-lye as polymeric xylan with an anhydroxylose-lignin ratio of 6.5. Xylan with a weight-average molar mass of 20 kDa was quantitatively precipitated from the solution previously concentrated from 7.4 to 37 g/L. The anhydroxylose-lignin ratio in the carbohydrate fraction increased to 29 g/g upon precipitation. Enzymatic hydrolys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Hemicelluloses in rapeseed straw consist of xylan and glucomannan . A common method to extract hemicelluloses is through hydrothermal extraction. Possible applications of hemicelluloses include oxygen barrier films, hydrogels, and reinforcement fillers in plastics. …”
Section: Introductionmentioning
confidence: 99%
“…Hemicelluloses in rapeseed straw consist of xylan and glucomannan . A common method to extract hemicelluloses is through hydrothermal extraction. Possible applications of hemicelluloses include oxygen barrier films, hydrogels, and reinforcement fillers in plastics. …”
Section: Introductionmentioning
confidence: 99%
“…Based on the studies referred above, an extensive modeling work has been recently conducted by Nieminen et al (2014a,b) . To benefit from the increased polysaccharide retention at elevated alkalinity in kraft cooking, dissolved hemicelluloses should be recovered through enhanced readsorption onto the fibers ( Yllner and Enstr ö m 1956 ;Aurell 1965 ;Meller 1968 ;Ribe et al 2010 ) or through separate isolation purification methods by membrane separation ( Arkell et al 2014 ;Testova et al 2014 ) followed by precipitation ( Liu et al 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…For alkali hemicellulose extraction from birch wood, Testova et al [32] reported that a high level of recovering can be obtained since only 2% of the residual sodium hydroxide remained in the concentrated fraction after sequential nano-and diafiltration. Schild et al [33] also reported an efficient separation of xylan from strong alkaline solutions through ultrafiltration in bench-scale experiments.…”
Section: Hemicellulose Extraction and Precipitation Yieldsmentioning
confidence: 99%